2017
DOI: 10.1093/biolinnean/blw052
|View full text |Cite
|
Sign up to set email alerts
|

Body size in the ant-associated isopod Platyarthrus hoffmannseggii is host-dependent

Abstract: Many symbionts live in association with different species. It can be expected that these distinct hosts might have a different effect on key life-history traits of the associated symbionts. Here, we compared the key trait body size of the obligatorily ant-associated isopod Platyarthrus hoffmannseggii collected in nests of two types of sympatric ant hosts. This isopod species showed surprisingly large differences in body size depending on type of host ant, with the head width of females and males associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Several authors have suggested that body size also affects the interactions between social insects and their guests [ 2 , 4 , 13 , 14 , 43 , 68 , 69 ]. Parmentier et al recently provided the first quantitative evidence for this relationship in wood ant-associated guests ([ 70 , 71 ]; but see also [ 72 ]). In fact, most social insect guests appear to be smaller than their hosts and diminutive body size is common [ 2 , 4 , 13 , 14 ], likely impeding recognition and thus protecting the intruders from attacks by host workers [ 2 , 14 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested that body size also affects the interactions between social insects and their guests [ 2 , 4 , 13 , 14 , 43 , 68 , 69 ]. Parmentier et al recently provided the first quantitative evidence for this relationship in wood ant-associated guests ([ 70 , 71 ]; but see also [ 72 ]). In fact, most social insect guests appear to be smaller than their hosts and diminutive body size is common [ 2 , 4 , 13 , 14 ], likely impeding recognition and thus protecting the intruders from attacks by host workers [ 2 , 14 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most social insect guests appear to be smaller than their hosts and diminutive body size is common [ 2 , 4 , 13 , 14 ], likely impeding recognition and thus protecting the intruders from attacks by host workers [ 2 , 14 , 73 ]. However, body size has not been studied intensively as a predictor of host attacks [ 14 , 70 – 72 ], and it remains largely unclear whether this trait is indeed related to host tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). It is a small, white, and blind oniscid isopod that is widely-distributed in Europe and strictly associated with various ant species (e.g., Mathes and Strouhal 1954 ; Gruner 1966 ; Parmentier et al 2017 ). A few other species are found in the Mediterranean region, e.g., Platyarthrus schoebli Budde-Lund, 1879 ( Garci and Cruz 1986 ), which can be easily differentiated from Platyarthrus hoffmannseggii .…”
Section: Discussionmentioning
confidence: 99%
“…Bibliography: Mac Leod (1880) , Moniez (1886) , Pelseneer (1886), Preudhomme de Borre (1886b) , Lameere (1895, 1897) , Maitland (1897), Schouteden (1901) , Bagnall (1907), Massart (1912) , Collart (1936) , Lameere (1938) , Adam and Leloup (1940) , Capart (1942), Polk and Van Oye (1956) , Polk (1957, 1959a,b) , Kersmaekers and Deroeck (1973) , Tavernier (1981) , Tavernier and Wouters (1989, 1991), Boon et al (1993) , Wouters et al (2000) , Dekoninck et al (2007) , Segers (2015), De Smedt et al (2017a) , Parmentier et al (2017) .…”
Section: Discussionmentioning
confidence: 99%